Implementasi Peraturan Pemerintah Nomor 94 Tahun 2021 Tentang Disiplin Pegawai Negeri Sipil Perspektif Fikih Siyasah Tanfidziyah - Yuman Rahmandha; Thoha Andiko; Imam Mahdi (CV. Doki Course and Training, 2024)
This study aims to solve problems related to the implementation of Government Regulation Number 94 of 2021 concerning Civil Servant Discipline from the perspective of fiqh siyasah at the Secretariat of the Regional People's Representative Council (DPRD) of Seluma Regency. Civil Servant Discipline is the rules and actions implemented to maintain discipline and behavior in accordance with norms and ethics in the civil servant work environment. Civil servant discipline is regulated in laws and government regulations in force in the country. Fiqh Siyasah is the management of general problems for the state with an Islamic nuance that guarantees the realization of benefits and avoids harm without violating sharia provisions. The research conducted was field research with a qualitative method with a normative approach and comparative law. Data were obtained through various methods, namely observation, interviews, documentation and literature studies. Data were analyzed using interpretation techniques to reveal the ontological, epistemological, and axiological essences related to the research objectives. This study found that the implementation of the discipline of government regulation number 94 of 2021 concerning Civil Servant Discipline article 8 paragraph 1 letter a in the Secretariat of the Regional People's Representative Council (DPRD) has been implemented but is not optimal. In terms of the duties and functions of Civil Servants at the Seluma Regency DPRD Secretariat, it is good but still not optimal, because there are still violations committed by Civil Servants but have not been prosecuted in accordance with applicable regulations. The results of this study state that Civil Servants at the Seluma Regency DPRD Secretariat do not fully apply the principle of